2013
DOI: 10.1002/eat.22132
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorder risk behavior and dental implications among adolescents

Abstract: In this study, a severe risk behavior for EDs was significantly associated with TE, but not with DC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
52
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 31 publications
8
52
2
3
Order By: Relevance
“…With regard to anorexia, the study shows that 33% of those surveyed presented a condition suggestive of developing eating disorders, of which the majority were women and within the age In the present study, there was no association between dental erosion and behavioral risk for eating disorders, unlike results reported by another Brazilian study with adolescents 22 and other international studies that point out a possible causal relationship between eating disorders and dental erosion 23 . It should be noted that the association was confirmed in some studies.…”
contrasting
confidence: 86%
See 3 more Smart Citations
“…With regard to anorexia, the study shows that 33% of those surveyed presented a condition suggestive of developing eating disorders, of which the majority were women and within the age In the present study, there was no association between dental erosion and behavioral risk for eating disorders, unlike results reported by another Brazilian study with adolescents 22 and other international studies that point out a possible causal relationship between eating disorders and dental erosion 23 . It should be noted that the association was confirmed in some studies.…”
contrasting
confidence: 86%
“…This examination was performed in another room of the school, and the teenager was seated in front of the examiner. The index used corresponds to the evaluation of the buccal and palatal surfaces of the four upper incisors (11,12,21,22) and occlusal surfaces of the first permanent molars (16,26,36,46). Data was recorded by a calibrated assistant.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Johansson et al [15] showed that eating disorders 8.5 times increase the risk of such erosion. Hermont et al [19] found erosion in 45% of the people affected, contrary to the healthy individuals in whom 8.8% had such lesions. Still, Uhlen et al [20] noted erosion in nearly 70% of patients affected with eating disorders.…”
mentioning
confidence: 94%